TiO2-PLLA nanocomposite coatings and free-standing films by a combined electrophoretic deposition-dip coating process - Chavez-Valdez, Alejandra; Arizmendi-Morquecho, Ana; Moreno, K. J.; Roether, Judith; Kaschta, Joachim; Boccaccini, Aldo R. (Composites Part B-Engineering, 2014)
TiO2/PLLA nanocomposites were prepared using a two-step process involving electrophoretic deposition (EPD) and dip coating (DC). EPD was carried out first to obtain porous TiO2 nanostructured coatings while subsequent dip coating was performed using different concentrations of PLLA in dichloromethane (DCM) to obtain nanocomposite materials. According to SEM images, cracks in the TiO2 nanostructured coatings, developed upon drying, were filled with the polymer which led to improvement of the flexibility of the nanocomposite coatings. Similarly, a surface modification from hydrophilic to hydrophobic was obtained with the addition of the polymer. FTIR analysis showed characteristic bands of both materials, TiO2 and PLLA, both on the coating surface and at the interphase between the nanocomposite coating and the substrate. Hardness measurements showed a maximum value of 1.4 GPa for TiO2–10 wt% PLLA composite. For DMTA tests, detached layers were used and the storage and loss moduli were determined. TiO2–PLLA nanocomposite coatings showed higher values of storage modulus at higher temperature in comparison to pure PLLA samples. Also, there was a shift in the glass transition temperature (Tg) with increasing TiO2 content. In conclusion, the EPD–DC combined technique proposed here enables the fabrication of nanostructured coatings and free-standing layers in which the quantity of PLLA can be changed according to the intended application, i.e. it is possible to fabricate coatings with tailored degradability and suitable mechanical properties with low additions of PLLA or free standing films with increased flexibility, biodegradability and biocompatibility with high amounts of PLLA.
Keywords: B. Mechanical properties; B. Surface properties; A. Nanostructures; A. Particle-reinforcement; Electrophoretic deposition